2007
DOI: 10.1016/j.jasms.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coulombic repulsion on the dissociation pathways and energetics of multiprotein complexes in the gas phase

Abstract: Thermal dissociation experiments, implemented with blackbody infrared radiative dissociation and Fourier-transform ion cyclotron resonance mass spectrometry, are performed on gaseous protonated and deprotonated ions of the homopentameric B subunits of Shiga toxin 1 (Stx1 B 5 ) and Shiga toxin 2 (Stx2 B 5 ) and the homotetramer streptavidin (S 4 ). Dissociation of the gaseous, multisubunit complexes proceeds predominantly by the loss of a single subunit. Notably, the fractional partitioning of charge between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
72
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 41 publications
9
72
0
Order By: Relevance
“…This indicates that one streptavidin monomer is sufficiently flexible so as to unfold to produce a surface area commensurate with the remaining trimer fragment ion. This interpretation is consistent with the electrostatic model calculations of Sinelnikov et al [15], who showed that a partially unfolded monomer subunit could account for the observed charge ratios. Interpreted in another way, the monomer need unfold only to the extent of making its surface area commensurate with the remaining trimer fragment ion.…”
Section: Application Of the Coulomb Repulsion Modelsupporting
confidence: 92%
See 4 more Smart Citations
“…This indicates that one streptavidin monomer is sufficiently flexible so as to unfold to produce a surface area commensurate with the remaining trimer fragment ion. This interpretation is consistent with the electrostatic model calculations of Sinelnikov et al [15], who showed that a partially unfolded monomer subunit could account for the observed charge ratios. Interpreted in another way, the monomer need unfold only to the extent of making its surface area commensurate with the remaining trimer fragment ion.…”
Section: Application Of the Coulomb Repulsion Modelsupporting
confidence: 92%
“…As the charge asymmetry increases, so does the barrier to dissociation. This is also consistent with the experimental results of Sinelnikov et al [15] who assert that the long-range repulsion between charged groups dominate the dissociation of a number of protein complexes, and who sought to understand the relationship between measured activation energies and some calculated values of this repulsion. It should also be noted that this long-range repulsion is generally the same regardless of how the charges q 1 and q 2 are distributed, since the repulsion between two uniformly charged spheres with charges q 1 and q 2 is the same as that between two point charges.…”
Section: Coulomb Repulsion Modelsupporting
confidence: 89%
See 3 more Smart Citations